RANCANG BANGUN SISTEM KEAMANAN PINTU RUMAH PURWARUPA DENGAN PENGENALAN WAJAH MENGGUNAKAN METODE TRIANGLE FACE - Nursaid, Muhammad Ibrahim; Taqwa, Ahmad; -, Sholihin (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2020)
We have already discussed the development of technology which is now opening fast, therefore for some people must anticipate this technological progress specifically on the security system section. Therefore the security system is gathered by various innovations created by humans. It is expected to get maximum results so that system break-ins do not occur that we do not expect. The security system that we will use is Face Recognition Biometrics Technology that is using various physical characteristics of humans. In its application, face recognition is done by using a camera or webcam to capture the image of someone who will later be stored in a database. In this study, a system designed to test someone using the Triangle Face method. Identifying faces is done by connecting features on a person's face such as the distance between the eyes, the distance on the left, the distance on the right, the left on the mouth, the distance on the right so that it will be created on the edge with the front and in front of the different. This system also uses a relay module and Solenoid Door Lock, to control a system that uses a Mini PC or called Raspberry Pi.